Thirteen [compact disc, unabridged] - Morgan, Richard K., 1965- (Tantor, 2007)
The subject of a failed government experiment to produce a more deadly military warrior, Carl Marsalis is a hit man who has lost his taste for killing, but when he is arrested in Miami, government officials come up with a plan to use his talents to achieve their own ends.